Reciprocal relations between cardiovascular disease, employment, financial insecurity, and post cardiac event recovery among Māori men: a case series. - Lisipeki S; Masters-Awatere B; Hodgetts D; Liew TV (BioMed Central Ltd, part of Springer Nature, 2023)
BACKGROUND: Disparities in cardiovascular outcomes between Māori and non-Māori persist despite technological advances in the treatment of cardiovascular disease and improved service provision. Little is known about how social determinants of health, such as income [in]security affect Māori men's access, treatment, and recovery from cardiovascular disease. This paper explores the contexts within which cardiovascular disease is experienced and healthcare becomes embedded. METHODS: This study utilized a case-comparative narrative approach to document and make sense of the patient experiences of four male Māori patients who, in the previous 6 months, had come through cardiac investigation and treatment at Waikato Hospital, a large tertiary cardiac center in New Zealand. Participant accounts were elicited using a culturally patterned narrative approach to case development, informed by Kaupapa Māori Research practices. It involved three repeat 1-3-hour interviews recorded with participants (12 interviews); the first interviews took place 5-16 weeks after surgery/discharge. RESULTS: Each of the four case studies firstly details a serious cardiac event(s) before describing the varying levels of financial worry they experienced. Major financial disruptions to their lives were at the forefront of the concerns of those facing financial insecurity-as opposed to their medical problems. Financial hardship within the context of an unresponsive welfare system impacted the access to care and access to funding contributed to psychological distress for several participants. Economic security and reciprocal relationships between employers and employees facilitated positive treatment experiences and recovery. CONCLUSION: Findings suggest that although multiple factors influence participant experiences and treatment outcomes, financial [in]security, and personal income is a key determinant. The heterogeneity in participant narratives suggests that although general inequities in health may exist for Māori as a population group, these inequities do not appear to be uniform. We postulate diverse mechanisms, by which financial insecurity may adversely affect outcomes from treatment and demonstrate financial security as a significant determinant in allowing patients to respond to and recover from cardiovascular disease more effectively.
Keywords: Cardiovascular disease; Health disparities; Income; Māori; Humans; Male; Cardiovascular Diseases; Employment; Maori People; Financial Stress